Integration of the Confucian Culture on Cross-Cultural Conflict Management: The Role of the COVID-19 Pandemic - Liu, Xiaoqin; Zhu, Wenzhong; Liang, Yanmei (Frontiers in Psychology, 2021)
Cross-culture conflict management is the major challenge for the Chinese enterprises going global along the Belt and Road Initiative. This study explores the feasibility of integrating the Confucian culture into cross-culture conflict management, and a special role is given to the COVID-19 pandemic. We combine the Confucian culture values and Hofstede's cultural dimension theory and adopt the questionnaire survey methods on the Chinese multinational enterprises' employees. The Cronbach's Alpha method is also deployed to test the reliability and validity of the data. We find the significant integration of the Confucian culture into cross-culture conflict management. Furthermore, 16 sub-values of the Confucian culture are suggested to mitigate the cross-culture conflicts in multinational enterprises effectively. The findings imply that the Chinese enterprises should consider new strategies to manage the cross-culture conflicts, especially during the COVID-19 pandemic.